PROFITABILITY, COMPANY SIZE, AND PROFIT PERSISTENCE INFLUENCE EARNING RESPONSE COEFFICIENT - Fatmawati, Mira; Nugroho, Danang; Novesar, Muhammad Refki; Nurhayati, Tita; Rizkiyah, Tiara Fitri; Pratama, Angga (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
The purpose of this study is to find out how Profitability, Firm Size, and Profit Persistence affect theEarnings Response Coefficient. In this research, the sample is made up of companies in the consumergoods sector that were listed on the Indonesia Stock Exchange from 2017 to 2021. The sample is madeup of 16 companies that meet the sample criteria, which were set using a method called "purposivesampling." Profitability, as measured by the Return on Assets ratio, company size, as measured by theNatural Logarithm, and profit persistence, as measured by the regression coefficient between earningsin the current period and earnings in the past period, are the independent variables of this study. TheEarnings Response Coefficient, which is measured by Abnormal Return and a few other stages, is thething that this study is based on. The study's results show that: (1) Profitability has a small positiveeffect on the earnings response coefficient; (2) Firm size has a negative and significant effect on theearnings response coefficient; and (3) Profit persistence has a negative and significant effect on theearnings response coefficient